Numerical modelling of detonation reaction zone of nitromethane by EXPLO5 code and wood and kirkwood theory - Štimac, Barbara (2021)
The detonation reaction zone of nitromethane (NM) has been extensively studied both experimentally and theoretically. The measured particle velocity profile of NM shows the existence of a sharp spike followed by a rapid drop over the first 5-10 ns (fast reaction). The sharp spike is followed by a gradual decrease (slow reactions) which terminate after approximately 50-60 ns when the CJ condition is attained. Based on experimental data, the total reaction zone length is estimated to be around 300 μm. Some experimental observations, such as the reaction zone width and the diameter effect, can be satisfactorily reproduced by numerical modelling, provided an appropriate reaction rate model is known. Here we describe the model for numerical modelling of the steady state detonation of NM. The model is based on the coupling thermochemical code EXPLO5 with the Wood-Kirkwood detonation theory, supplemented with different reaction rate models. The constants in the rate models are calibrated based on experimentally measured particle velocity profiles and the detonation reaction zone width. It was found that the model can describe the experimentally measured total reaction time (width of reaction zone) and the particle velocitytime profile of NM. It was found also that the reaction rate model plays a key role on the shape of the shock wave front. In addition, the model can predict the detonation parameters (D, pCJ, TCJ, VCJ, etc.) and the effect of charge diameter on the detonation parameters.